Brain size and organization in the Middle Pleistocene hominins from Sima de los Huesos. Inferences from endocranial variation. Issue 129 (April 2019) - Poza-Rey, Eva María; Gómez-Robles, Aida; Arsuaga, Juan Luis
Abstract: The Sima de los Huesos (SH) endocranial sample includes 16 complete or partial endocasts corresponding to European Middle Pleistocene hominins. Different anatomical and molecular studies have demonstrated that these hominins are phylogenetically related to Neanderthals, thus making them the earliest unquestionable representatives of the Neanderthal lineage. The description of endocranial variation in this population is fundamental to shedding light on the evolution of the Neanderthal brain. In this contribution, we analyze and describe endocranial variation in this sample, including aspects related to brain size (endocranial volume and encephalization) and brain organization (through qualitative descriptions and quantitative analyses). Our results indicate that the SH hominins show a transitional state between a primitive hominin endocranial configuration (which is found in Homo erectus and non-SH Middle Pleistocene Homo ) and the derived configurations found in Neanderthals and modern humans, without a clear anticipation of classic Neanderthal endocranial traits. In comparison with other cranial and postcranial traits that show a fully Neanderthal or clear pre-Neanderthal condition in the SH collection, endocranial variation in these hominins is surprisingly primitive and shows no Neanderthal affinity. These results and the comparison with other cranial traits confirm that Neanderthals evolved in a mosaic fashion. Traits related to mastication (dental, facial and mandibular anatomy) led the Neanderthalization process, whereas neurocranial anatomy must have acquired a fully Neanderthal condition considerably later.